Harmonic Comparison of Three Phase Direct Matrix Converter for Reactive Load with Balance and Unbalance Supply Voltage - Kandasamy K.V; Sarat Kumar Sahoo (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This paper presents harmonic analysis of matrix converter using different control technique for balance and Unbalance three phase input voltage of reactive load. Since Matrix converter is subject to affected either by external disturbance or by load conditions. Due to this the supply voltage becomes unbalance. This cause improper switching of matrix converter results higher harmonics. This harmonics are harmful to the quality of the output power. The switching sequence of the matrix converter is controlled by vector control method. Different control technique is proposed in this paper to get optimized result with reduced harmonic for unbalanced and balance input voltage using PID, Fractional Order PID (PIλDδ) controller (FOPID), Particle Swarm Optimization (PSO)FOPID. PID control technique result are compared with other optimization technique for best optimum output. The FOPID controller is used to compensates the current and also improvise the quality of energy by reducing the harmonic content. The simulations and hardware results will be presented and interpreted. The effectivess of the proposed system is proven with the results is shown in this paper which produce a better steady state lesser transient rather than the conventional PID method.